Systemic injection of AAV9-GDNF provides modest functional improvements in the SOD1(G93A) ALS rat but has adverse side effects - Thomsen, G M (Gene Ther, 2017)
Injecting proteins into the central nervous system that stimulate neuronal growth can lead to beneficial effects in animal models of disease. In particular, glial cell line-derived neurotrophic factor (GDNF) has shown promise in animal and cell models of Parkinson's disease, Huntington's disease and amyotrophic lateral sclerosis (ALS). Here, systemic AAV9-GDNF was delivered via tail vein injections to young rats to determine whether this could be a safe and functional strategy to treat the SOD1(G93A) rat model of ALS and, therefore, translated to a therapy for ALS patients. We found that GDNF administration in this manner resulted in modest functional improvement, whereby grip strength was maintained for longer and the onset of forelimb paralysis was delayed compared to non-treated rats. This did not, however, translate into an extension in survival. In addition, ALS rats receiving GDNF exhibited slower weight gain, reduced activity levels and decreased working memory. Collectively, these results confirm that caution should be applied when applying growth factors such as GDNF systemically to multiple tissues.